PENERAPAN PENDEKATAN PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIK DAN KEMANDIRIAN BELAJAR SISWA MA - Irpan Mulyana; Tatan Supyan; Luvy Sylviana Zhanty (Journal on Education, 2019)
The purpose of this study is to illustrate the application of the problem solving approach to improve the mathematical creative thinking ability of MA students. The research method used was an experiment, where subjects in this population were chosen randomly, namely class XI-IPS 1 and class XI-IPS 2 Ma Al Maa`uun Mande Cianjur. In this research, the researcher gives the same treatment to the subject of the researcher to further know the effect of the treatment is the problem solving approach in the experimental class and conventional learning in the control class. Mathematics learning using the problem solving approach is more effective in the application of the problem solving approach to improve mathematical creative thinking abilities and the independence of MA students there is a comparison compared to ordinary learning. the application of the problem solving approach to improve the mathematical creative thinking ability of MA students is better than ordinary learning. The magnitude of the increase in students' mathematical creative thinking abilities taught by learning mathematics using the problem solving approach is 81 and ordinary learning is 78. The magnitude of the increase in the independence of mathematical learning of students who are taught mathematics learning problem solving is 83 and ordinary learning is 80.